A real option-based valuation model for Shared Water Saving Management Contract. (20th March 2021) - Hu, Hao; Wang, Xiaosheng; Gao, Zhichao; Guo, Haiying
Abstract: Water Saving Management Contract (WSMC) is believed as an efficient water-saving model and developed in recent years. However, because the high upfront investment cost and great uncertainty of WSMC, the static evaluation methods have defects in evaluating the return on investment of WSMC projects. Real option theory makes up for these defects and is applied in this paper with the expectation to evaluate the uncertainty of a Shared WSMC project and the economic feasibility of investing in the project. First, a new expression of volatility is presented based on the characteristics of Shared WSMC projects. The volatility contains uncertainties in water price, the amount of water-saving, waterborne fee, and operating & maintenance cost simultaneously. Then, it is assumed that the water saving service company is entitled options to abandon and expand the Shared WSMC project during the contract period. Based on the existing model, the exercise prices of the two options are improved. Furthermore, the real option value (ROV) of a Shared WSMC project is solved using the binomial tree option pricing model, and the economic feasibility of the project is comprehensively evaluated by combining with the static net present value and ROV organically. Finally, the Shared WSMC project of the Hebei University of Engineering in China is studied to verify the validity of the proposed method. The obtained results indicate that the economic value of the Shared WSMC project is expanded by the ROV, which means that additional value can be gained through flexible strategies and management in the context of uncertainty. Besides, the additional economic benefits of the two options vary significantly for different Shared WSMC projects. Expand option is particularly essential when Shared WSMC projects with a considerable return on investment. Conversely, the abandon option should be taken seriously. Especially when both options are considered together, the additional economic benefits are sub-additive. Highlights: Based on Monte Carlo simulation, the volatility of project value is measured synthetically by several key factors. The time value of the fund is emphasized according to different discount rates, and then the exercise price is determined. The model of option pricing with modified volatility and exercise price is applied to the Shared WSMC project firstly.